Research on ultra-sensitive refractive index sensor based on a homogeneous polymer nine-liquid-core photonics crystal fiber - Gurui Fu (Elsevier, 2021)
Owing to photonics crystal fiber (PCF) microfluidic sensors pose great merits of low sample consuming, light weight and portable. They are expected to become on-chip biomedical point-of-care testing (POCT) devices. However, relative low sensing sensitivity of some reported PCF microfluidic sensors can bring great challenges in monitoring early-stage physical diseases, environmental pollution and food safety. Herein, we propose an ultra-sensitive homogeneous nine-liqiud-core fiber (NLCF) microfluidic sensor with a low-index Teflon cladding. When aqueous solution is injected into nine core of the fiber, the light can be excited in the central core and coupled to other surrounding cores along the area of NLCF. More importantly, compared with reported various PCF microfluidic sensors, a much improved sensitivity of 39391 nm/RIU is numerically and theoretically realized based on coupled mode theory (CMT) through using finite element method (FEM). Therefore, this work opens up significant opportunities to develop new ultra-sensitive on-chip optical microfluidic sensors.